The setting configuration in ‘The picture of Dorian Gray’ by Oscar Wilde - Pereira, Tiago Ferreira; Jappe, Rodrigo (Disciplinarum Scientia | Ciências Humanas, 2019)
This article shows how the narrative chronotope characterizes other dimensions of the text and the way this relation influences the construction of meaning during the reading process. In literary narratives, the dimensions of space lay the foundations of the fictional world. By the construction of places in a certain time, the author creates a scenery in which his characters develop in the plot. Oscar Wilde’s novel ‘The Picture of Dorian Gray’ is set in England in the late 19th century. This article concludes that the setting has an important role in the meaning-make process in which the reader engages while reading.